1989
DOI: 10.1021/jf00088a017
|View full text |Cite
|
Sign up to set email alerts
|

Terminal apiose: a new sugar constituent of grape juice glycosides

Abstract: Apiose [3-(hydroxymethyl) -D-erythrofuranose] has been identified as a component of the carbohydrate moiety of glycosides from the juice of Muscat grapes by acid hydrolysis, alditol acetate derivatization of liberated sugars, and GC-MS. Permethylation of the bulk of glycosides and subsequent GC-MS analysis of the partially methylated alditol acetates showed that apiose was under terminal nonreducing position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
2
5
0
1
Order By: Relevance
“…Apiose was the only pentose residue identified in the sample. Analysis of the mass spectrum showed that the ion distribution of the apiose residue derived from DCPA was similar to a terminal apioside residue (Table 4) reported by Brillouet et al [29]. The chromatogram of derivatized carbohydrate residues was dominated (44% of integrated area) by 1,6-linked glucose residues further supporting designation of a glucopyranosyl-(6→1)-apiofuranoside.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Apiose was the only pentose residue identified in the sample. Analysis of the mass spectrum showed that the ion distribution of the apiose residue derived from DCPA was similar to a terminal apioside residue (Table 4) reported by Brillouet et al [29]. The chromatogram of derivatized carbohydrate residues was dominated (44% of integrated area) by 1,6-linked glucose residues further supporting designation of a glucopyranosyl-(6→1)-apiofuranoside.…”
Section: Resultssupporting
confidence: 78%
“…Comparison of ion distribution of 1-linked apiose fromBrillouet et al[29] and pentosyl residue reported by the Complex…”
mentioning
confidence: 99%
“…Monoterpenyl sugar conjugates in grapes include 6-O-b-L-rhamnopyranosyl-D-glucopyranoside, 6-O-b-L-arabinofuranosyl-D-glucopyranoside, and 3-(hydroxy-methyl)-D-erythrofuranose (Williams et al, 1982b;Brillouet et al, 1989). For complete enzymatic hydrolysis of conjugated monoterpenes to occur, the 1-6 intersugar linkage must initially be cleaved by either a-arabinosidase, b-apiosidase, or a-L-rhamnosidase.…”
Section: Introductionmentioning
confidence: 99%
“…Ils existent sous la forme libre (linalol, α-terpinéol, nérol, géraniol) et sous la forme de mono et di-glucosides, inodores. Leur libération par voie enzymatique peut avoir lieu aussi bien grâce à des ß-glucopyranosidases végétales ou celles périplasmiques de Saccharomyces cerevisiae, après intervention de ß-D-apiofuranosidase, de α-L-arabinofuranosidase ou de α-L-rhamnopyranosidase qui détachent le glucide terminal (BAYONOVE et al, 1971(BAYONOVE et al, , 1984WILLIAMS et al, 1980WIL-SON et al, 1984, 1986ARYAN et al, 1987 ;BIRON et al, 1988 ;DARRIET et al, 1988 ;NOBLE et al, 1988 ;STRAUSS et al, 1988 ;GÜNATA, 1994 ;GÜNATA et al, 1985bGÜNATA et al, , 1988GÜNATA et al, , 1989COR-DONNIER et al, 1989 ;BRILLOUET et al, 1990 ;VOIRIN et al, 1990 ;MATEO et DI STEFANO, 1997).…”
Section: Connaissances Sur La Contribution De La Levure Dans La Libérunclassified